A review of polymer composite materials in bulletproof vest to defense sector - Olivia Thresnayu Cahayaputri; Riri Murniati; Sovian Aritonang; Aditya Tri Oktaviana (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2023)
Personal protection, especially in the context of military protection and security, became a major focus in the development of bulletproof vests. Polymer composite materials offer a wide range of advantages in terms of strength, density, and ability to reduce the kinetic energy of projectiles, making them an attractive choice for such protection applications. This study examines the different types of polymers and composite technologies used in the manufacture of bulletproof vests. This study examines the use of polymer composite materials in the manufacture of bulletproof vests used in the defense sector. We evaluate the mechanical, thermal, and ballistic properties of these materials and investigate the design approaches applied to improve the performance of these protectors. The research proved that the composite was efficient enough to be used as a bulletproof vest material because it was light, flexible and strong.